Do Overcrowding and Turnover Cause Violence in Prison? - Baggio, Stéphanie; Peigné, Nicolas; Heller, Patrick; Gétaz, Laurent; Liebrenz, Michael; Wolff, Hans (Frontiers in Psychiatry, 2020)
Violence is common in prison and its individual risk factors are well documented. However, there is a mixed evidence on the relationship between prison violence and institutional factors, such as overcrowding and turnover, and recent research suggested that these factors may not be important or relevant. This study investigated the association between prison violence and institutional factors in a Swiss pre-trial prison between 2013 and 2018. Measures included violence (assaults requiring immediate medical attention) as well as the annual overcrowding and turnover rates. Using a meta-regression, the results showed that prison violence was higher when overcrowding and turnover increased. Overall, our study highlighted that institutional prison factors might have notable detrimental effects on prison life. Reduction of prison overcrowding and turnover appear critical to reduce prisoners’ vulnerability and staff safety. Turning prison into safe places designed to promote desistance would probably not be achievable without considering these crucial factors.